Fatty Acid Composition and Regulatory Gene Expression in Late-Term Embryos of ACRB and COBB Broilers - Su, Shengchen; Wang, Yidi; Chen, Chongxiao; Suh, Miyoung; Azain, Michael; Kim, Woo Kyun (Frontiers in Veterinary Science, 2020)
Cobb broilers (COBB) have been heavily selected for their production performance in the past several decades, while the Athens Canadian Random Bred (ACRB) chickens, a meat-type breed, have been kept as a non-selected control strain. The purpose of this study was to compare these two lines of chickens at late-embryonic development and identify the molecular markers and fatty acid profiles underlining their differences in growth performance due to selection. Fertilized eggs of the ACRB (n=6) and COBB (n=6) were used at 14 and 18 embryonic days. Genes involved in lipogenesis and myogenesis were measured using quantitative real-time RT-PCR, and fatty acid (FA) compositions of egg yolk, muscle, and liver were measured using gas-chromatography. COBB had higher egg weight, embryo weight, and breast and fat ratio. The gene expression in the liver showed an interaction between age and breed on FASN expression with the highest level in COBB at E18. ACRB had higher Apo-B and MTTP expression, but lower SREBP-1 expression compared to COBB. No difference was found in myogenesis gene expression in the muscle between two breeds. For the FA composition, muscle was largely affected by both breed and age. Yolk and liver were affected mainly by breed and age, respectively. Constant interaction effects in docosahexaenoic acid (DHA), indicating the highest level in all the tested tissues of ACRB at E14 and the constant main effects with higher myristic, palmitic and gondoic, but lower linolenic acid in the liver and yolk of COBB compared to in those of ACRB. At last, fat accumulation in the liver had no obvious difference between the breeds but was higher when embryo was older. In conclusion, broiler breed affects egg, embryo and tissue weight, as well as FA composition in initial egg yolk and throughout the embryonic development. The highest docosahexaenoic percentage was observed in ACRB, indicating that genetic selection may result in fatty acid profile changes such as lower DHA content in chicken tissues and eggs.